Socioeconomic status, multiple autonomy support attunement, and early adolescents' social development - Simões, F.; Calheiros, M. M.; Alarcão, M. M. A. (Journal of Community Psychology, 2018)
This study explores the relationship between socioeconomic status (SES), Multiple Autonomy Support Attunement (MASA) and social development indicators (antisocial behavior, prosociality, and self-regulation), considering the concurrent effects of structural (gender and age) and social factors (social networks' size and orientation). MASA describes patterns of autonomy support provided by different sources, which in this case were parents, teachers, and mentors. Participants were 645 adolescents (M = 12.30; SD = .60; 55.35% girls). Using Latent Class Analysis LCA), a four-class solution for MASA presented the best fit. A Generalized Linear Model (GLM) approach revealed that lower SES was associated with greater antisocial behavior, while MASA was linked to improved prosociality and self-regulation when youths were included in a high-attuned multiple autonomy support class, compared to other MASA classes. Thus, optimal levels of MASA can represent an asset for training, implementation, and assessment stages of interventions aimed at improving early adolescents' positive social development.